Neuroleptic malignant syndrome following catatonia: Vigilance is the price of antipsychotic prescription. (2nd March 2017) - Reilly, Thomas J; Cross, Sean; Taylor, David M; Haslam, Richard; Tomlin, Sophie C; Gaastra, Benjamin
Objectives: To describe a case of neuroleptic malignant syndrome following antipsychotic treatment of catatonia, highlighting the potentially serious complications of this rare adverse drug reaction. Methods: We present a case report of a patient who developed this syndrome with various sequelae. Results: The patient developed neuroleptic after being treated with lorazepam and olanzapine for catatonia. He subsequently developed the complications of rhabdomyolysis, acute kidney injury, pulmonary embolism, urinary retention and ileus. He received high-dose lorazepam, anticoagulation and intravenous fluids. Antipsychotic medication in the form of haloperidol was reinstated with no adverse effect, and he went on to make a full recovery. Conclusions: This case illustrates the potential life-threatening complications of neuroleptic malignant syndrome and the need for a low index of clinical suspicion. It also highlights the lack of evidence for treatment of catatonia, including the use of antipsychotics.